Analysis of the proliferative activity in lung adenocarcinomas with specific driver mutations - Kriegsmann, Mark; Harms, Alexander; Kazdal, Daniel; Fischer, Sebastian; Stenzinger, Albrecht; Leichsenring, Jonas; Penzel, Roland; Longuespée, Rémi; Kriegsmann, Katharina; Muley, Thomas; Safi, Seyer; Warth, Arne (Pathology, research and practice, 2018)
In the last decade it became evident that many lung adenocarcinomas (ADC) harbor key genetic alterations such as KRAS, EGFR or BRAF mutations as well as rearrangements of ROS1 or ALK that drive these tumors. In the present study we investigated whether different driver mutations of ADC result in different proliferation rates, which might have clinical impact, including resistance to therapy, recurrence and prognosis. We analyzed the proliferation index (PI) on full slides of surgically resected ADC (n=230) with known genetic aberrations by means of immunohistochemistry and subsequent digital image analysis and correlated the results with clinicopathological variables including overall (OS) and disease free survival (DFS). We did not observe significant differences in OS or DFS regarding the KRAS or EGFR mutational status (P=0.56). However, KRAS mutated ADC showed an increased PI compared to EGFR mutated ADC, and ADC with ALK translocations (P<0.01). Subgroup analysis of EGFR mutated ADC showed a higher PI for tumors harboring a mutation in exon 18 and 20, compared to tumors with a mutation in exon 19 or 21. A PI of 11.5% was the best possible prognostic stratificator for OS (P=0.01 in KRAS mutated and P<0.01 in EGFR mutated ADC). In conclusion, the PI differs significantly among ADC with distinct driver mutations. This might explain the varying indications for a prognostic relevance of the PI observed in prior studies. Our study provides a basis for the establishment of a reliable and clinically meaningful PI threshold.